Amylase testing on intimate samples from pre-pubescent, post-pubescent and post-menopausal females: implications for forensic casework in sexual assault allegations. Issue 6 (1st November 2020) - Sari, Daliya; Hitchcock, Catherine; Collins, Sienna; Cochrane, Clint; Bruce, David
ABSTRACT: The determination of the biological source of DNA recovered from exhibits in forensic investigations has become crucial information to either support or refute allegations in a criminal trial. In particular, this information could add value to court evidence relating to alternative scenarios e.g. direct versus indirect DNA transfer etc. However, it is well known that α-amylase, the marker used for the detection of saliva, is found in bodily fluids and secretions other than saliva, including vaginal secretions. This has significant implications in the investigation of alleged sexual assaults involving oral contact with the genitalia of females of all ages. However, no empirical data was available as to whether α-amylase was also present at detectable levels in vaginal secretions of pre-pubescent children or post-menopausal adult females. Therefore, the main aim of this project was to determine whether there are detectable levels of α-amylase in female vaginal secretions at different stages of physiological sexual maturity. The results of this investigation inform laboratory practice regarding the evidentiary value of detecting α-amylase by Rapid Stain Identification of Human Saliva (RSID™-Saliva) Kit in allegations of sexual assault where saliva may have been deposited directly (oral sexual assault) or indirectly (as a lubricant).